Ruthenium Incorporated Cobalt Phosphide Nanocubes Derived From a Prussian Blue Analog for Enhanced Hydrogen Evolution - Yan, Yingzhang; Huang, Jinzhen; Wang, Xianjie; Gao, Tangling; Zhang, Yumin; Yao, Tai; Song, Bo (Frontiers in Chemistry, 2018)
Electrochemical water splitting in alkaline media plays an important role in mass production of hydrogen. Ruthenium (Ru), as the cheapest member of platinum-group metals, has attracted much attention, and the incorporation of trace amount of Ru with cobalt phosphide could significantly improve the hydrogen evolution reaction (HER) catalytic activity. In this work, ruthenium-incorporated cobalt phosphide nanocubes are synthesized via a reaction between Co–Co Prussian blue analogue (Co-PBA) and ruthenium chloride (RuCl3) followed by the phosphidation. The sample with a Ru content of ~2.04 wt.% exhibits the best HER catalytic activity with a low overpotential of 51 and 155 mV, to achieve the current densities of -10 and -100 mA cm-2, respectively, and the Tafel slope of 53.8 mV dec-1, which is comparable to the commercial Pt/C. This study provides a new perspective to the design and construction of high performance electrocatalysts for HER and other catalytic applications in a relatively low price.